Sensemaking and sustainability: a sensemaking perspective on the ethical use of big data in marketing strategizing - Wang, Emma (Junhong); Berthon, Pierre; Su, Yiran (Sustainable Development Seen Through the Lenses of Ethnoeconomics and the Circular Economy, 2024)
Despite the ethical concerns over the datafication and surveillance of individuals and groups, companies are making ever greater investments in big data. The assumptions underpinning this movement are: (1) organizations are passive implementers of big data—more data is the inevitable consequence of technology and a competitive necessity for business, (2) more data offers a more objective and accurate picture of reality and (3) more data enables better prediction. We argue that this perspective is strategically unsustainable and abdicates ethical responsibility.
Keywords: Big Data; Organization; Sensemaking; Strategizing; Sustainability; dept.mrk

The impact of generative AI on syllabus design and learning - Kim, Hyoseok; Koo, Thomas K. B. (Journal of Marketing Education, 2024)
This research examines the impact of generative artificial intelligence (AI) on the perception of educational content quality, specifically by comparing AI-generated and human-generated course syllabi in marketing education. Results from four studies indicate a general preference for AI-generated syllabi, attributed to their greater perceived objectivity. This preference is more pronounced in conventional courses but diminishes in unconventional ones, suggesting that the unique aspects of these courses may reduce the advantages of generative AI. In addition, disclosing the AI authorship of syllabi significantly affects their perceived quality negatively, underscoring the impact of transparency on the acceptance of AI-generated educational materials. These findings highlight the potential of generative AI in educational content creation and its limitations in certain contexts. They offer valuable insights for enhancing educational practices and shaping policy decisions to enrich student experiences in the era of AI integration.
Keywords: dept.mrk; peer-reviewed